Nanomaterial FET-based biosensor for Medical Applications - Rahimunnisa, K. (Journal of Electronics and Informatics, 2022)
For distinct properties and advantages like easy integration, high sensitivity, portability, and good selectivity, FET (Field-effect transistors) find application in varied fields and research areas. Especially, in biomedical applications, a drastic improvement is seen with the evolution of FET where Nanomaterial-based Bio-FET is an outstanding performer for their biosensing ability. In medical field, such Nanomaterial FET-Biosensor is carried out for performing label-free biomolecule sensing to screen out different diseases. Including infectious disease detection like virus infection, and bacterial infection, glucose, and diabetic levels can be screened as well with the aid of FET-based biosensor. This paper concentrates on the basic concepts, working principle of Bio-FET, recent research of FET in medical area, challenges and future scope of Nanomaterial-based Bio-FET.